Unconventional Functions of Mitotic Kinases in Kidney Tumorigenesis - Hascoet, Pauline; Chesnel, Franck; Le Goff, Cathy; Le Goff, Xavier; Arlot-Bonnemains, Yannick (Frontiers in Oncology, 2015)
Human tumours exhibit a variety of genetic alterations, including point mutations, translocations, gene amplifications and deletions, as well as aneuploid chromosome numbers. For carcinomas, aneuploidy is associated with poor patient outcome for a large variety of tumour types, including breast, colon and renal cell carcinoma. The Renal cell cancer (RCC) is a heterogeneous carcinoma consisting of different histologic types. The clear renal cell carcinoma (ccRCC) is the most common subtype and represents 85 % of the RCC. Central to the biology of the ccRCC is the loss of function of the Von Hippel Lindau gene but is also associated with genetic instability that could be caused by abrogation of the cell cycle mitotic spindle checkpoint and may involve the Aurora kinases, which regulate centrosome maturation. Aneuploidy can also result from the loss of cell-cell adhesion and apical-basal cell polarity that also may be regulated by the mitotic kinases (Plk1, CK2, DLCK1 and Aurora kinases). In this review, we describe the “non mitotic” unconventional functions of these kinases in renal tumourigenesis.